PANDEMIC COVID-19, STOCK TRADE VOLUME, AND MARKET CAPITALIZATION ON SHARE RETURN - Hastuti, Rini Tri; Stephanie, Crystalice (Graduate Program of Universitas Tarumanagara, 2025)
Instruments in the capital market consist of stocks, mutual funds, bonds, derivative instruments, Exchange Traded Funds (ETF) and other securities. In investing, investors and potential investors must first understand the risk profile so that they can then decide which instruments are suitable for investing. Starting at the end of 2019 the world was shocked by a global epidemic. This outbreak is called Coronavirus Disease (Covid-19). Due to the significant increase in positive cases, Large-Scale Social Restrictions (PSBB) were implemented starting from April 10 2020 until April 23 2020. This condition has had an impact on the investment world, especially in the capital market. This impact is reflected in the fluctuations in the share price of the investment instrument. Other factors that can affect stock prices in the capital market, namely stock trading volume and market capitalization. This study was conducted with the aim of knowing and proving whether there is an influence of daily growth in positive Covid-19 confirmed cases, stock trading volume and market capitalization on stock returns contained in the LQ-45 index on the Indonesia Stock Exchange (IDX) starting from February 3, 2020 to January 31, 2022. In this study, it used a non-probability sampling method to determine the sample to be used. This study used 35 samples of companies that had been selected through the criteria specified in this study. In this study, collecting secondary data and the data that has been obtained will be processed using Microsoft Excel and also Eviews software version 10. The results of this study show that the growth of positive daily cases of Covid-19, trading volume and market capitalization negatively affects stock returns.